2015
DOI: 10.1073/pnas.1506415112
|View full text |Cite
|
Sign up to set email alerts
|

Increasing intracellular trehalose is sufficient to confer desiccation tolerance to Saccharomyces cerevisiae

Abstract: Diverse organisms capable of surviving desiccation, termed anhydrobiotes, include species from bacteria, yeast, plants, and invertebrates. However, most organisms are sensitive to desiccation, likely due to an assortment of different stresses such as protein misfolding and aggregation, hyperosmotic stress, membrane fracturing, and changes in cell volume and shape leading to an overcrowded cytoplasm and metabolic arrest. The exact stress(es) that cause lethality in desiccation-sensitive organisms and how the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 30 publications
3
132
2
Order By: Relevance
“…Gluconeogenesis occurred during TRI degradation as indicated by high RPKM values of gluconeogenesis‐related genes ( eno , gpm I, fda ), which are associated with SUC metabolism (Table S2). Trehalose is also one of the representative alpha‐linked disaccharides synthesized intracellularly that helps cells to adapt to various stressors such as oxidative, heat, osmotic and desiccation stress (Benaroudj et al ., ; Purvis et al ., ; Doehlemann et al ., ; Tapia et al ., ). Trehalose measurement was performed using wild type and the otsA ‐disrupted strain.…”
Section: Resultsmentioning
confidence: 97%
“…Gluconeogenesis occurred during TRI degradation as indicated by high RPKM values of gluconeogenesis‐related genes ( eno , gpm I, fda ), which are associated with SUC metabolism (Table S2). Trehalose is also one of the representative alpha‐linked disaccharides synthesized intracellularly that helps cells to adapt to various stressors such as oxidative, heat, osmotic and desiccation stress (Benaroudj et al ., ; Purvis et al ., ; Doehlemann et al ., ; Tapia et al ., ). Trehalose measurement was performed using wild type and the otsA ‐disrupted strain.…”
Section: Resultsmentioning
confidence: 97%
“…Trehalose functions as a protector for cell membranes and cellular proteins under environmental stresses such as heat, cold, desiccation, dehydration, ethanol, oxidation and anoxia. 22,26,27 In yeast, trehalose level is low under favorable growth condition but is induced by environmental stresses. However, Ratnakumar and Tunnacliffe 28 suggested that there was no consistent relationship between intracellular trehalose concentration and desiccation tolerance in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…One way in which trehalose protects cells is by initiating controlled autophagy, thereby avoiding uncontrolled damage that would otherwise trigger programmed cell death (Williams et al, 2015). Trehalose also confers desiccation tolerance on yeast cells (Tapia et al, 2015), in part by protecting them from oxidative damage by reactive oxygen species (Benaroudj et al, 2001). Many of the abiotic (and biotic) stresses faced by plants lead to reactive oxygen species production, and the accumulation of sugars such as trehalose and Suc is one of the mechanisms providing protection from oxidative stress (Romero et al, 2002;Cortina and Culianez-Macia, 2005;CouĂ©e et al, 2006;Luo et al, 2008;Chen and Hoehenwarter, 2015).…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%